2019
DOI: 10.1213/xaa.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

The Ventrain Device: A Future Role in Difficult Airway Algorithms?

Abstract: The Ventrain is a small, manually operated, single-use, inspiratory flow-adjustable ventilation device that generates positive pressure during inspiration and, through a Bernoulli effect within the device, active suction during expiration. It was designed to provide emergency ventilation during airway obstruction via narrow-bore cannulae. The device has been used successfully in elective procedures lasting >1 hour. It remains to be seen if its theoretical advantages in “can’t intubate, can’t oxygenate” (CIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 275 If needle cricothyrotomy is used, ventilation should ideally proceed using a Ventrain device (Ventinova Medical, Eindhoven, Netherlands). 276 , 277 For older children (i.e., > 8–12 yr), the scalpel-bougie technique can be used via the CTM. There is no evidence that cricothyrotomy kits are superior to a scalpel cricothyrotomy technique.…”
Section: The Pediatric Patient—special Considerationsmentioning
confidence: 99%
“… 275 If needle cricothyrotomy is used, ventilation should ideally proceed using a Ventrain device (Ventinova Medical, Eindhoven, Netherlands). 276 , 277 For older children (i.e., > 8–12 yr), the scalpel-bougie technique can be used via the CTM. There is no evidence that cricothyrotomy kits are superior to a scalpel cricothyrotomy technique.…”
Section: The Pediatric Patient—special Considerationsmentioning
confidence: 99%
“…The clinical application of Ventrain, including its potential advantages over alternative techniques, has been described in detail [2]. Several studies have demonstrated that Ventrain is the safest and most efficient device for ventilation in a (near) complete airway obstruction [3][4][5], and its successful use in emergency situations has been published [6,7].…”
mentioning
confidence: 99%